People’s perception and involvement in improving urban greenery in Benin (West Africa) - Akakpo, Bokon Alexis; Okhimamhe, Appollonia A.; Orekan, Vincent A. O. (My University, 2023)
Urban sustainable development is a feat to achieve, particularly within African nations. Current patterns of urban expan- sion are creating multiple problems to urban greenery and quality of life. Assuming urban resident’s perception varies between and within cities, this paper claims to document resident’s perceptions on the existing greenery spaces, the prerogative for environmental safeguard, and the determinant of resident’s willingness for urban greenery improvement within the cities of Parakou and Porto-Novo in Benin. A semi-structured interview was randomly conducted with 400 peo- ple including residents and institution officers in each city. The data collected are related to socio-economic characteristics and the perception on urban greenery characteristics, urban greenery importance and urban greenery management and planning. The test χ2 was applied to understand the independence between cities and city boroughs. Correspondence analysis was also used to display some relationships and binary logistic regression to examine the variables that explain people’s willingness to get involved in improving urban greenery in each city. The results revealed that around 80% of existing urban greeneries are mostly located in the core of the town and the state of the density and diversity of these greenery areas were differently perceived in the districts of each city. The main benefits lost from urban greenery were air quality (45.25%) for Parakou and cooling effect (74%) for Porto-Novo and the causes of these losses depended also on the cities and the districts within the cities. Public participation was perceived to be low (> 85%) and the institutional cooperation with local communities, educational level and knowledge on greening main impacts must be improved to foster the involvement of people in urban greenery development. This study is relevant to support literature data and to further studies. It will also serve as a guideline for policymakers, urban planners, and managers, cityscape architects, and projects of urban sustainability regarding the urban greenery in Benin.
Keywords: Urban greenery · Resident’s perception · Benefits lost · Public involvement · Determining factors · Benin